2022
DOI: 10.1371/journal.pone.0274138
|View full text |Cite
|
Sign up to set email alerts
|

Time since faecal deposition influences mobilisation of culturable E. coli and intestinal enterococci from deer, goose and dairy cow faeces

Abstract: Mobilisation is a term used to describe the supply of a pollutant from its environmental source, e.g., soil or faeces, into a hydrological transfer pathway. The overarching aim of this study was to determine, using a laboratory-based approach, whether faecal indicator bacteria (FIB) are hydrologically mobilised in different quantities from a typical agricultural, wildlife and wildfowl source, namely dairy cattle, red deer and greylag goose faeces. The mobilisation of FIB from fresh and ageing faeces under two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…All faeces were collected fresh for use in experiments, and the provenance of all faecal sources and sample collection is detailed in full in Afolabi et al [ 10 ]. Briefly, fresh dairy faeces were collected from the livestock housing of a conventional dairy farm in Stirlingshire, Scotland.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All faeces were collected fresh for use in experiments, and the provenance of all faecal sources and sample collection is detailed in full in Afolabi et al [ 10 ]. Briefly, fresh dairy faeces were collected from the livestock housing of a conventional dairy farm in Stirlingshire, Scotland.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to agricultural and sewage sources, FIO loading of watercourses and streambed sediments can also originate from wildlife and wildfowl. Populations of deer, geese, and other wildlife may defecate directly into an aquatic environment, or their faecal depositions to land can be disrupted following rainfall events, with a proportion of FIOs subsequently mobilised and transferred to receiving waters [ 10 ]. Studies have reported on black-tailed deer and Canadian geese as contributors of FIOs in environmental matrices [ 11 , 12 ], and there are reports of increased FIO inputs to sediment stores of aquatic environments in catchments that can result from wildlife activity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%